Attitudes Toward Women's Marital Name Choices - Laurie K. Seheuble; David R. Johnson (Names, 1998)
Abstract Attitudes of more than 900 adult respondents toward women's choosing to retain their birth name as their last name when they marry are reported. The majority of respondents were tolerant ofa woman's keeping her birth name, but were not tolerant if the couple planned to have children. Women were far more accepting of a wife's retaining her birth name than were men. Also more tolerant were persons with higher levels of education, higher incomes, lived in larger communities, had more liberal political leanings, were less religious and younger.